Psychosocial impacts on the Christchurch Muslim community following the 15 March terrorist attacks: a mixed-methods study protocol. Issue 10 (1st October 2021) - Sulaiman-Hill, Ruqayya C.; Porter, Richard; Tanveer, Sandila; Boden, Joseph; Beaglehole, Ben; Schluter, Philip J; Dean, Shaystah; Bell, Caroline
Abstract : Introduction: On 15 March 2019, a white supremacist gunman opened fire in two mosques in Christchurch, New Zealand, during Friday prayers, killing 51 people and injuring 40. The event was witnessed by at least 250 survivors and also live streamed on social media, leading to widespread and repeated exposure within the community. It is expected that survivors, families and community members will be at increased risk of developing mental disorders due to the scale and violence of these attacks. This protocol describes the first phase of a proposed longitudinal study to screen and assess the long-term impacts of the terrorist attack on members of the Christchurch Muslim community, to determine clinical need and facilitate access to appropriate interventions and to gain insights into working with such a traumatised, ethnically diverse population. It has been developed in close collaboration with members of that community. Methods and analysis: A mixed-method design is described, combining self-report measures with a clinician-administered diagnostic interview. Participants include Christchurch Muslims aged 18 years and over, with a target sample size of n=200. Analyses will determine prevalence of major mental disorders, while regression analyses will model the relationship between pre-event features, trauma exposure and mental disorders. A small number of participants, stratified by exposure type, will also take part in a qualitative interview in English. All study information and self-report measures are provided in translations based on the ethnolinguistic composition of the group and are available in paper and online versions. Ethics and dissemination: Ethical approval was granted by the New Zealand Health and Disability Ethics Committee 19/NTA/147. All participants provide informed consent, either written or online via REDCap software. Findings will be disseminated initially to the impacted community, then by publication in scientific journals, presentations and to government agencies. Trial registration number: The study is registered with the Australian New Zealand Clinical Trials Registry, ACTRN12620000909921.